Economic growth and transport and communications infrastructure in Peru - Machado, Roberto (2017)
This research aims to measure the contribution of public investment in transport and communications infrastructure to economic growth in the regions of Peru. This is done on the basis of different estimations using panel data for the 24 regions of Peru, over the period 2004- 2014. First, a conventional fixed-effect panel data method is used for the estimations, whereby investment in transport and communications infrastructure is found to have a positive effect on GDP and GDP per worker in the regions. Then, a spatial panel data methodology is followed, which takes into account the direct effects of investment in infrastructure within a region, as well as the indirect effects that occur between regions. Here, the results suggest that investment in transportation has a direct positive effect on regional GDP, while investment in communications contributes to GDP indirectly.